The career prospects of overeducated Americans - Brian Clark; Clément Joubert; Arnaud Maurel (IZA Journal of Labor Economics, 2017)
In this paper we analyze career dynamics for US workers who have more schooling than their peers in the same occupation. We use data from the NLSY79 combined with the CPS to analyze transitions into and out of overeducated employment, together with the corresponding effects on wages. Overeducation is a fairly persistent phenomenon at the aggregate and individual levels, with 66% of workers remaining overeducated after 1 year. Overeducation is not just more common but also more persistent among blacks and low-AFQT individuals. Further, the hazard rate out of overeducation drops by about 60% during the first 5 years spent overeducated. However, the estimation of a mixed proportional hazard model suggests that this is attributable to selection on unobservables rather than true duration dependence. Lastly, overeducation is associated with lower current as well as future wages, consistent with scarring effects.
Keywords: J24; I21; 330; Human capital; Earnings dynamics; Overeducation